Phosphorus availability and dynamics in soil affected by long-term ruzigrass cover crop - Almeida, Danilo S.; Menezes-Blackburn, Daniel; Zhang, Hao; Haygarth, Philip M.; Rosolem, Ciro A. (Geoderma, 2019)
The use of grasses as cover crops in the off-season of cash crops under no-till has been largely adopted. However, soil phosphorus (P) uptake was previously shown to be reduced when ruzigrass is introduced in the rotation, affecting the viability and sustainability of this cropping system. The objective of this study was to assess the effect of ruzigrass on soil P availability and desorption kinetics under different P fertilizer application rates. A long-term field experiment where soybean (Glycine max) has been grown in rotation with ruzigrass (Urochloa ruziziensis) or fallow for 10 years, with the application of 0, 13, and 26 kg ha−1 of P, was evaluated for two consecutive years. Soil P desorption kinetics was assessed using diffusive equilibrium (DET) and gradient in thin films (DGT) techniques, as well as the DGT-induced fluxes in soils model (DIFS). Microbial biomass P (MBP) was assessed to verify if soil solution P (PDET) was reduced due to immobilization by microorganisms. Ruzigrass reduced MBP and PDET especially when P fertilizer was applied. The concentration of labile P (PDGT) was also lower after ruzigrass than in fallow. The soil ability to resupply P to soil solution was lower after ruzigrass regardless of P rates due to a slower desorption in response to the perturbation imposed by DGT. Growing ruzigrass as cover crop in the soybean off-season decreases soil P availability regardless of P fertilizer application rates by fundamentally reducing P mobility and P resupply from soil solid phase into soil solution. •The use of ruzigrass as cover crop affect soil P availability in the long-term.•Soil P desorption kinetics was assessed using diffusive gradient in thin films (DGT).•The use of DGT provided new insights into P availability, by considering the P diffusion and resupply process.•Ruzigrass decreases P availability by reducing P mobility and resupply from soil solid phase into soil solution.